Calcium hydroxyapatite-based photocatalysts for environment remediation: Characteristics, performances and future perspectives. (15th May 2017) - Piccirillo, C.; L. Castro, P.M.
Abstract: Calcium hydroxyapatite Ca10 (PO4 )6 (OH)2 (HAp) is a material widely used in biomedicine, for bone implants manufacture, due to its biocompatibility. HAp has also application for environmental remediation, as it can be employed as metal removal; moreover, it has the capability of effectively adsorbing organic molecules its surface. In recent years, the photocatalytic properties of HAp have been investigated; indeed several studies report of HAp used as photocatalyst, either on its own or combined with other photocatalytic materials. Although in the majority of cases the activity was induced by UV light, some reports of visible light-activated materials were reported. Here we present a critical review of the latest developments for HAp-based photocatalysts; the materials discussed are undoped single phase HAp, doped HAp and HAp-containing composites. For undoped single phase HAp, the possible surface treatment and lattice defects which can lead to a photoactive material are discussed. Considering doped HAp, the use of Ti 4+ (the most common dopant) is described, with particular attention to the effects that this metal have on the characteristics of the material (i.e. crystallinity) and on its photocatalytic behaviour. The use of other dopants is also discussed. For the multiphasic materials, the combination of HAp with other photocatalysts is discussed, mainly but not only with titanium dioxide TiO2 . Overall, HAp is a compound with high potential as photocatalyst; this property, combined with its capability for heavy metal removal, makes it a multifunctional material for environmental remediation. As future perspectives, further studies, based on the results obtained until present, should be performed, to improve the performance of the materials and/or shift the band gap into the visible. The use of other dopants and/or the combination with other photocatalysts, for instance, are features which is worth exploring. Highlights: Hydroxyapatite (HAp) based materials with photocatalytic properties are reviewed. Undoped, doped and multiphasic HAp-containing photocatalysts are described. Applications for environment remediation in liquid and gas phases are discussed. A comparison between the different photocatalytic HAp is performed. HAp potential a multifunctional material for decontamination is reviewed.